Implementation of Wideband Radar ECM–ECCM on NRSM Unmanned Ground Vehicle (UGV) - Muda, Nur Rachman Supadmana (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
The rapid evolution of radar-based surveillance and targeting systems poses significant challenges to the survivability of unmanned ground vehicles (UGVs) operating in contested electromagnetic environments. This study presents the implementation framework of a wideband Radar Electronic Countermeasure–Electronic Counter-Countermeasure (ECM–ECCM) system integrated into an NRSM-class UGV, operating across a frequency range of 27 MHz to 10 GHz. The proposed system adopts a modular and software-defined architecture, enabling adaptive threat detection, real-time response, and electromagnetic resilience. The research focuses on system design, integration methodology, and performance evaluation using defined electronic warfare metrics. The results demonstrate that wideband ECM–ECCM integration significantly enhances UGV survivability and operational effectiveness against modern radar threats.